Serum Soluble ST2 Is a Valuable Prognostic Biomarker in Patients With Acute Heart Failure - Wang, Zeyu; Pan, Xin; Xu, Hong; Wu, You; Jia, Xiaomin; Fang, Yiling; Lu, Yi; Xu, Yawei; Zhang, Ji; Su, Yang (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: This study aimed to investigate the clinical utility of different soluble suppression of tumorigenicity 2 (sST2) levels in assessing the severity and prognosis of patients with acute heart failure (AHF). Methods: This was a prospective cohort study. Three hundred and thirty-one consecutively enrolled AHF patients from March 2018 to November 2019 were divided into 3 subgroups according to sST2 levels: T1 (1.15-7.70 ng/ml; N = 110), T2 (7.71-17.24 ng/ml; N = 111), and T3 (17.26-47.42 ng/ml; N = 110). The patients were followed up for a median period of 21.0 months for the development of the primary endpoint. Cox proportional hazards model was performed to evaluate the prognostic value of sST2 for the clinical outcomes. Results: The mean age of patients was 69 years (range, 34 - 93 years), and 70.4% were male. During the follow-up period, 63 participants died. Patients with higher sST2 levels had lower left ventricular ejection fraction (correlation = -0.119, P = 0.031), and higher New York Heart Association classification (correlation = 0.443, P ＜ 0.001) and N-terminal pro-B type natriuretic peptide (NT-proBNP) levels (correlation = 0.392, P ＜ 0.001). Higher sST2 was also associated with creatinine, urea nitrogen, hemoglobin, and left ventricular mass index. Multivariate analysis revealed that sST2 (per log unit, hazard ratio: 2.174, 95% confidence interval [CI] 1.012-4.67, P = 0.047) and NT-proBNP (per log unit, HR 2.171, 95%CI 1.169-4.032, P<0.001) were independent risk factors for the primary outcome in all patients with AHF. Conclusion: sST2 can provide prognostic information in AHF. The higher the sST2 level in patients with AHF, the higher the incidence of cardiovascular death.